2019
DOI: 10.3343/alm.2019.39.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin Levels and Indoleamine 2,3-Dioxygenase Activity as Biomarkers of Immune System Activation and Childhood Allergic Diseases

Abstract: Background Although Th2 immune activation is predominant in allergic diseases, neopterinlevels and indoleamine 2,3-dioxygenase (IDO)-1 activity (kynurenine:tryptophan ratio), which reflect Th1 immune activity, increase with interferon-gamma (IFN-γ) stimulation. We investigated neopterin, tryptophan, and kynurenine levels as biomarkersof the Th1 immune system activation and changes in IDO-1 activityin children with asthma, allergic rhinitis, and atopic dermatitis, as well as the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…They can make full use of the inhaled drugs. And children's immune system is constantly improving (26), which maintains immune balance and alleviates the Th1/Th2 cell imbalance, so that asthma symptoms are relieved (27, 28). Some studies reported that asthma control is related to the season, temperature, humidity and pollen (2933).…”
Section: Discussionmentioning
confidence: 99%
“…They can make full use of the inhaled drugs. And children's immune system is constantly improving (26), which maintains immune balance and alleviates the Th1/Th2 cell imbalance, so that asthma symptoms are relieved (27, 28). Some studies reported that asthma control is related to the season, temperature, humidity and pollen (2933).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported significantly increased tryptophan levels in atopic children and adults. In a non-metabolomic study of 205 children, tryptophan and its downstream metabolite kynurenine were significantly higher in asthmatic children, allergic children, and in children with AD compared to HCs [ 42 ]. The highest tryptophan levels were observed in children with asthma, and in line with Saude et al [ 24 ], tryptophan levels could significantly discriminate between controlled and uncontrolled asthma [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human studies also support a tolerogenic role for IDO and a reduction in IDO activity in people with asthma. In a study of 205 children, tryptophan and kynurenine levels were higher and IgE and IDO activity lower in those with asthma and allergic rhinitis [85]. In another pediatric population, IDO activity in peripheral blood and induced sputum was lower in children with allergic asthma than healthy controls [86].…”
Section: Tryptophanmentioning
confidence: 95%